Disrupting ceramide-CD300f interaction prevents septic peritonitis by stimulating neutrophil recruitment - Izawa, Kumi; Maehara, Akie; Isobe, Masamichi; Yasuda, Yuka; Urai, Makoto; Hoshino, Yasutaka; Ueno, Keigo; Matsukawa, Toshihiro; Takahashi, Mariko; Kaitani, Ayako; Shiba, Emiko; Takamori, Ayako; et al. (Scientific Reports, 2017)
Sepsis is a serious clinical problem. Negative regulation of innate immunity is associated with sepsis progression, but the underlying mechanisms remains unclear. Here we show that the receptor CD300f promotes disease progression in sepsis. CD300f (-/-) mice were protected from death after cecal ligation and puncture (CLP), a murine model of septic peritonitis. CD300f was highly expressed in mast cells and recruited neutrophils in the peritoneal cavity. Analysis of mice (e.g., mast cell-deficient mice) receiving transplants of wild-type or CD300f (-/-) mast cells or neutrophils indicated that CD300f deficiency did not influence intrinsic migratory abilities of neutrophils, but enhanced neutrophil chemoattractant production (from mast cells and neutrophils) in the peritoneal cavity of CLP-operated mice, leading to robust accumulation of neutrophils which efficiently eliminated Escherichia coli. Ceramide-CD300f interaction suppressed the release of neutrophil chemoattractants from Escherichia coli-stimulated mast cells and neutrophils. Administration of the reagents that disrupted the ceramide-CD300f interaction prevented CLP-induced sepsis by stimulating neutrophil recruitment, whereas that of ceramide-containing vesicles aggravated sepsis. Extracellular concentrations of ceramides increased in the peritoneal cavity after CLP, suggesting a possible role of extracellular ceramides, CD300f ligands, in the negative-feedback suppression of innate immune responses. Thus, CD300f is an attractive target for the treatment of sepsis.
EVALuna2:25887